Applications of the scoliosis width-to-length ratio for guiding selection of the surgical approaches of degenerative lumbar scoliosis - Jiang, Chuan-jie (BMC Musculoskelet Disord, 2016)
BACKGROUND: There does not exist a comprehensive parameter for guiding selection of short or long segment fusion for degenerative lumbar scoliosis (DLS). The aim of our study was to investigate the applications of the width-to-length ratio in guiding selection of the surgical approaches for DLS. METHODS: A retrospective analysis was performed of 142 patients with DLS who underwent operative treatments from July 2000 to January 2012. The scoliosis width-to-length ratios were measured and used as a grouping criterion of surgical approaches. The Oswestry disability index (ODI) was used to evaluate the clinical outcomes. Radiological parameters such as Cobb’s angle of main curve, Cobb’s angle of compensatory curve were all measured. RESULTS: For patients with width-to-length ratio less than 0.36, the short segment group had better short-term postoperative outcomes with regard to Cobb’s angle of main curve, Cobb’s angle of compensatory curve and ODI scores compared to the long segment group. However, for patients with width-to-length ratio greater than 0.36, the postoperative outcomes for the long segment group were better compared to the short segment group. CONCLUSIONS: The scoliosis width-to-length ratio can provide a comprehensive preoperative assessment of the severity of the DLS and guiding selection of a therapeutic treatment regimen. Further studies with a larger number of samples and longer term of follow up are warranted.